Eﬀectiveness of Implementing Cultural Literacy Through Storytelling for Early Age Children at the Jakarta Methodist Kindergarten - Euis Agung Sari; NIta Priyanti; Debora Puji Widiati; Rizky Megawangi; Patimah; Oliviani Elen Komalig (Universitas Panca Sakti Bekasi, 2024)
His research evaluates the eﬀectiveness of the storytelling method as a strategy to increase the cultural literacy of young children at Methodist Kindergarten, Jakarta. With keywords such as regular schedules, relevant local content, parent participation, and use of technology, the results of interviews with kindergarten heads show that this method has proven successful. Integrating storytelling activities with the local context and active participation of parents at home is the key to success. These ﬁndings provide in- depth insight into culturally oriented learning strategies, providing a basis for developing a more contextual curriculum. This research also highlights the importance of using technology to support storytelling experiences, enrich children's cultural literacy and respond to cultural diversity in Indonesia. The conclusions of this research provide a signiﬁcant contribution to increasing cultural literacy and developing early childhood education.